PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER (NHT) MELALUI TUTOR TEMAN SEBAYA TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS IV SDN 08 DURIAN KAPEH - Lilik Syafriani; Inge Angelia; Thesa Kandaga (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Mathematics learning in elementary schools is still dominated by conventional teacher-centered methods, resulting in low student engagement and conceptual understanding. This study examines the effect of Numbered Head Together (NHT) cooperative learning model through peer tutoring on fourth-grade students' mathematics learning outcomes. The study employed a quasi-experimental design with a nonequivalent control group design. The population involved 35 fourth-grade students from SD Negeri 08 Durian Kapeh, divided into 20 students in the experimental class (NHT model with peer tutors) and 15 students in the control class (conventional learning). Data were collected through post-tests and analyzed using one-way ANOVA and effect size tests. Results showed a significant difference between both groups (F = 11.603; p = 0.002 < 0.05). Effect size analysis yielded η² = 0.260, ε² = 0.238, and ω² = 0.233, indicating a large effect. The NHT model through peer tutoring contributed approximately 23–26% to the improvement in mathematics learning outcomes. It is concluded that the NHT cooperative learning model through peer tutoring effectively improves students' mathematics learning outcomes. This model not only enhances active thinking and discussion but also develops cooperation, communication skills, and deep conceptual understanding of mathematics. It is recommended that teachers implement this model continuously by utilizing peer tutors, and future research can include additional variables such as learning motivation or critical thinking skills for more comprehensive results.